Avaliações farmacoeconômicas em vigilância de medicamentos - Abjaude, Samir Antonio Rodrigues [UNESP]; Varallo, Fabiana Rossi [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2014)
The study aimed to identify pharmacoeconomic studies in pharmacovigilance and to observe the economic outcomes in post-marketing surveillance. Therefore, a bibliographic survey was performed in databases Lilacs, PubMed/ Bireme. The search strategy was done by using scientific health descriptors [ "adverse drug reaction reporting systems " OR " medication errors " OR "product surveillance, postmarketing" OR " sentinel surveillance" ] AND [ " cost-benefit analysis" OR "cost efficiency analysis " OR " costs and cost analysis " OR " hospital costs " OR " cost-effectiveness " OR " cost-effectiveness evaluation " OR " drug costs " ]. Manuscripts published in the last 10 years were selected. We chose 13 articles, of which 12 corresponded to cost-benefit analysis and only one to cost-effectiveness assessment. In only one study there was no economy, all the other ones generated savings, ranging from 13.7 to 30% in spending valued service. Surveillance actions were: continuing education; active search through tracking devices and / or implementation of round; teamwork and multidisciplinary deployment; computerized security services management, enabling traceability of information and alerts. The results of the proposed actions have led to the prevention of adverse drug reactions, to decline of risks to the patient, to the reduction of inappropriate prescriptions, as well as the length of hospital stay spending valued service. Surveillance actions were: continuing education; active search through tracking devices and / or implementation of round; teamwork and multidisciplinary deployment; computerized security services management, enabling traceability of information and alerts. The results of the proposed actions have led to the prevention of adverse drug reactions, to decline of risks to the patient, to the reduction of inappropriate prescriptions, as well as the length of hospital stay

Propôs-se identificar estudos farmacoeconômicos em farmacovigilância e conhecer os resultados econômicos em vigilância pós-comercialização. Trata-se de uma revisão bibliográfica direcionada nas bases de dados Lilacs e PubMed/Bireme. Para a busca dos artigos utilizaram-se os seguintes descritores científicos em saúde: [“sistemas de notificação de reações adversas a medicamento” OR "erros de medicação" OR "vigilância de produtos comercializados" OR "vigilância de evento sentinela"] AND ["análise custo-benefício" OR "análise custo-eficiência" OR "custos e análise de custo" OR "custos hospitalares" OR "custo-efetividade" OR "avaliação de custoefetividade" OR "custos de medicamentos"]. Foram selecionados os manuscritos publicados nos últimos 10 anos. Foram selecionados 13 artigos, dos quais 12 realizaram análises de custo-benefício e apenas um de custo-efetividade. Apenas em um estudo não houve economia, os demais geraram economia, que variaram de 13,7 a 30% nos gastos do serviço avaliado. As ações de vigilância foram: educação continuada; busca ativa por meio de rastreadores e/ou implantação de ronda; trabalho em equipe e multidisciplinar; implantação do serviço informatizado de gestão de segurança, permitindo a rastreabilidade das informações e alertas. Os resultados das ações propostas levaram a prevenção de reações adversas a medicamentos, redução de risco ao paciente, diminuição de prescrições inadequadas e redução do tempo de internação.
Reviews on pharmacoeconomic drug surveillance
Keywords: Pharmacovigilance; Cost-benefit analysis; Cost efficiency analysis; Cost effectiveness evaluation; Farmacovigilância; Análise custo-benefício; Analise custo-eficiência; Avaliação de custo-efetividade